Improving the Technique of Driving the Ball When Playing Mini-Football for Players Aged 18-20 Years (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Today, mini-football is rightfully one of the most developing sports in Uzbekistan. It is integrated into almost all schools and universities, where multi-scale tournaments among students are held annually. But the stage of improving sports skills remains insufficiently studied, since futsal is a fairly young sport in which various game patterns appear every year, and most importantly, mini-football becomes more contact and high-speed.